Respuesta :
Answer:
x = 3
Step-by-step explanation:
Solve for x:
3 (3 - 3 x) = 2 (x + 3) - 30
2 (x + 3) = 2 x + 6:
3 (3 - 3 x) = 2 x + 6 - 30
Grouping like terms, 2 x - 30 + 6 = 2 x + (6 - 30):
3 (3 - 3 x) = 2 x + (6 - 30)
6 - 30 = -24:
3 (3 - 3 x) = 2 x + -24
Expand out terms of the left hand side:
9 - 9 x = 2 x - 24
Subtract 2 x from both sides:
9 + (-9 x - 2 x) = (2 x - 2 x) - 24
-9 x - 2 x = -11 x:
-11 x + 9 = (2 x - 2 x) - 24
2 x - 2 x = 0:
9 - 11 x = -24
Subtract 9 from both sides:
(9 - 9) - 11 x = -9 - 24
9 - 9 = 0:
-11 x = -9 - 24
-9 - 24 = -33:
-11 x = -33
Divide both sides of -11 x = -33 by -11:
(-11 x)/(-11) = (-33)/(-11)
(-11)/(-11) = 1:
x = (-33)/(-11)
The gcd of -33 and -11 is -11, so (-33)/(-11) = (-11×3)/(-11×1) = (-11)/(-11)×3 = 3:
Answer: x = 3
Answer:
x = 3
Step-by-step explanation:
Solve:
3(3 - 3x) = 2(x + 3) – 30 Remove parentheses
9 – 9x = 2x + 6 – 30 Combine like terms
9 – 9x = 2x – 24 Add 24 to each side
33 – 9x = 2x Add 9x to each side
33 = 11x Divide each side by 11
x = 3
Check:
3(3 - 3x) = 2(x + 3) – 30
3(3 – 3×3) = 2(3+ 3) – 30
3(3 – 9) = 2×6 – 30
3(-6) = 12 – 30
-18 = -18